Business Education Management in Patron-Client Relations: Business Ethics Among Middlemen at Kuta Market, Pemalang - Faqih Tsabitul Azmi; Nurfuadi Nurfuadi (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine the patron-client relationship in the trading practices of middlemen at the Kuta market in Pemalang. It examines how these relationships influence transaction dynamics, bargaining power, and economic dependency among micro-enterprises. This study also examines business ethics, including honesty, fairness, and responsibility in trading activities. Furthermore, it examines the role of management business education in shaping ethical practices and supporting the sustainability of micro-enterprises within traditional market settings. Methodology/approach: Data were collected through interviews, observations, and documentation. Results: The study shows hierarchical patterns in the patron-client system that hinder micro-enterprise autonomy. Conclusions: This study reveals that patron dominance in the tengkulak business limits client autonomy and ethical fairness, highlighting the need for improved community-based training and ethical practices. Limitations: This study was limited to a specific location and community; therefore, the findings cannot yet be generalized to other traditional market contexts in Indonesia. Contributions: This study contributes to the fields of educational business management and business ethics, particularly within the informal microeconomic sector. These findings provide conceptual and empirical insights into patron-client dynamics and related ethical challenges. Furthermore, this study offers valuable references for academics, policymakers, and community development institutions to understand and address ethical issues within patron-client systems in traditional markets.